Experimental study of the ignition and combustion characteristics of cattle manure under different environmental conditions. (15th April 2020) - Jiang, Chunlong; Lin, Qizhao; Wang, Chengxin; Jiang, Xuedan; Bi, Haobo; Bao, Lin
Abstract: This paper investigates the ignition and combustion characteristics of cattle manure particles under different environmental conditions, and analyses the ash produced by combustion. The cattle manure particles were fixed in a vertical heating furnace, and a thermocouple and camera recorded the internal temperature and combustion process of the particles. The environmental temperature of the combustion chamber was set at 873, 973 and 1073 K, and the oxygen concentrations were 10–80%; the gas flow rate was set to 10, 20 and 30 L/min, respectively. The experimental results show that the effect of environmental temperature on the ignition and combustion of cattle manure particles is most obvious. Under most circumstances, the volatile matter begins to ignite before the particulate matter. As the environmental temperature and oxygen concentration increase, the condition of ignition and combustion were improved, and the internal ignition temperature, ignition delay and volatile combustion time were reduced. In addition, thermogravimetric experiments on powdered cattle manure were also carried out at four heating rates, and four peaks were presented in the derivative thermogravimetric (DTG) curve, corresponding to four different stages of cattle manure combustion. Highlights: Thermogravimetric experiment and particle combustion experiment were combined. The ignition and combustion process of single cattle manure particles was detected. The skeleton of the single particles remained intact during burning process. The tendency of slagging and fouling of cattle manure ash is very low.